2020
DOI: 10.7759/cureus.9249
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Endometrial Stromal Sarcoma, Two Decades Post-Treatment

Abstract: Endometrial stromal cell sarcomas (ESS) are a unique subtype of uterine malignancy. Recurrent low grade endometrial stromal sarcomas (LESS) is identified in half of the patients. Here, we discuss a case of a 76-year-old Asian female with a past medical history of adenomyosis and hypertension who presented to the outpatient clinic with a chief complaint of painless hematuria for one day. Computed tomography scan of abdomen and pelvis with contrast showed a new right-sided mixed cystic and solid pelvic mass meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Hormonal therapy has also been used to shrink the tumor before surgical resection, as reported in the case of a 47-year-old woman with low-grade ESS [ 31 ]. Despite complete remission of ESS, such tumors carry a high risk of recurrence even after two decades of treatment, as reported by Gangireddy et al ., which highlights the importance of regular follow-ups [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal therapy has also been used to shrink the tumor before surgical resection, as reported in the case of a 47-year-old woman with low-grade ESS [ 31 ]. Despite complete remission of ESS, such tumors carry a high risk of recurrence even after two decades of treatment, as reported by Gangireddy et al ., which highlights the importance of regular follow-ups [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Their five-year survival rates are higher than 80%. For disease stages I and II the five-year survival is approximately 90% whereas for stages III and IV (i.e., advanced disease) the survival rate for the same interval of time is significantly reduced, according to the FIGO stage system [ 75 , 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…Total hysterectomy with bilateral salpingo-oophorectomy remains the standard treatment for ESS, and lymphadenectomy does not appear to improve overall survival rates [ 83 ]. Adjuvant radiotherapy and hormone therapy are not well-established therapeutic options yet, even though some studies have shown that hormonal agents can be an alternative to the management of LG-ESS [ 82 , 84 ]. In contrast, HG-ESS is generally detected in advanced stages with no effective adjuvant therapy available.…”
Section: Introductionmentioning
confidence: 99%